Effect of short-term cold-water immersion on muscle pain sensitivity in elite track cyclists - Klich, S.; Krymski, I.; Michalik, K.; Kawczynski, A. (Physical Therapy in Sport, 2018)
Objective: To determine the effect of short-term cold-water immersion (CWI) on muscle pain sensitivity after maximal anaerobic power training in track cyclists. Design: Repeated measures. Setting: University Laboratory. Participants: 12 elite sprint track cyclists (age 24,75±4,23 years). Main outcome measures: PPT measurements were made on dominant lower extremity (right) in 20 reference points, including anterior thigh muscles, posterior thigh muscles and posterior cuff muscles. PPT levels were measured: 1) before workout, 2) immediately after workout, but before CWI 3) 1h after CWI and 4) 12h after CWI. Mean PPT values for each muscle group per participant were calculated for further statistical analysis. Results: The average PPT for anterior thigh muscles decreased significantly after effort (p=0.001) and increased significantly 1h after CWI (p=0.048). In posterior thigh muscles PPT decreased significantly after effort (p=0.014) and increased significantly 1h and 12h after CWI (p=0.045 and p=0.25 respectively). However, in posterior cuff muscles PPT decreased only after effort (p=0.001). Conclusions:Short-term repeated sprint exercise appears to affect PPT in track cyclists. This study have reported that CWI in 5°C for 5min have had a beneficial effect in minimizing PPT 1h post repeated maximal sprint training.